2020
DOI: 10.3390/nu12092527
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Predictors of Overweight and Obesity among Young Children in the Children’s Healthy Living Study on Guam

Abstract: This study is part of the Children’s Healthy Living program in U.S. Affiliated Pacific region. The objectives were to estimate overweight and obesity (OWOB) prevalence and identify possible related risk factors among ethnic groups in Guam. In 2013, 865 children (2–8 years) were recruited via community-based sampling from select communities in Guam. Children’s demographic and health behavior information; dietary intake; and anthropometric measurements were collected. Logistic regression, odds ratio, t-tests, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 63 publications
(92 reference statements)
1
16
0
Order By: Relevance
“…The prevalence of early childhood overweight and obesity (OWOB) in 2011–2012 was 22.8% among 2–5 years old in the US [ 2 ]. In 2013, the OWOB prevalence among children 2–8 years old in Guam was 27.4% [ 3 ]. Early childhood obesity prevalence was also higher in Guam (13.2%) than the US (8.4%) during the same time and among similar ages [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of early childhood overweight and obesity (OWOB) in 2011–2012 was 22.8% among 2–5 years old in the US [ 2 ]. In 2013, the OWOB prevalence among children 2–8 years old in Guam was 27.4% [ 3 ]. Early childhood obesity prevalence was also higher in Guam (13.2%) than the US (8.4%) during the same time and among similar ages [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…In order to begin to fill this gap, this Special Issue on "Nutrition Among Vulnerable Populations" features papers quantifying dietary intake, nutritional status, access to food and food security, barriers to healthful foods and food security and environmental influences experienced by vulnerable groups with a high prevalence of food insecurity. The following sections summarize the findings of the four papers on children [13][14][15][16], three papers on adults [17][18][19] and three papers featuring studies of families or households (Figure 1) [20][21][22]. The diet, health and environmental associations linked with food insecurity or low resources among vulnerable child populations are featured in papers including samples drawn from rarely investigated young children living in Hawai'i, Guam and the Midwestern U.S., while a sample of children and adolescents included in the National Health and Nutrition Examination Survey (NHANES) provided nationally representative contrasts of the diets of food secure and insecure children.…”
mentioning
confidence: 99%
“…Surprisingly, findings showed that Native Hawaiian, Pacific Islander and Filipino infants ages 3 to 12 months from food insecure households consumed foods from more food groups and consumed fresh foods on a greater proportion of days compared with infants from food secure households [13]. A community-based sample of children 2 to 8 years old from Guam were the focus of another study evaluating health, lifestyle and dietary intake [15]. Approximately 80% were receiving food assistance, 51% experienced food insecurity and 27.4% were affected by overweight and obesity.…”
mentioning
confidence: 99%
See 2 more Smart Citations